2018
DOI: 10.1111/ggi.13559
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and prognostic implications of aspiration pneumonia in older hip fracture patients: A multicenter retrospective analysis

Abstract: Aim The present study aimed to investigate the risk factors and prognostic implications of aspiration pneumonia in older hip fracture patients. Methods A total of 394 female and 125 male hip fracture patients aged ≥60 years who underwent surgery between 2015 and 2018 were retrospectively analyzed. To identify risk factors of aspiration pneumonia, demographic factors, the American Society of Anesthesiologists classification, past medical history, known risk factors of aspiration and factors associated with surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 30 publications
(80 reference statements)
3
59
0
Order By: Relevance
“…Mental-cognitive factors such as perception of reality disorders and impaired cognition were independently associated with pressure ulcers and aspiration pneumonia. These results corroborate those of previous inquiries that identified delirium as a risk factor for these AEs [33,40]. Within the psycho-emotional domain, fear and anxiety were risk factors for falls.…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…Mental-cognitive factors such as perception of reality disorders and impaired cognition were independently associated with pressure ulcers and aspiration pneumonia. These results corroborate those of previous inquiries that identified delirium as a risk factor for these AEs [33,40]. Within the psycho-emotional domain, fear and anxiety were risk factors for falls.…”
Section: Plos Onesupporting
confidence: 90%
“…Regarding age, older patients exhibit a higher risk of becoming frail, of presenting comorbidities and experiencing AEs during hospitalization, probably because of their increased care needs [ 11 , 26 , 32 , 33 ]. A systematic review identified co-morbidity, reduced functional ability and lower quality of care as important causative factors associated with AEs [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for peri-operative pneumonia have been identified [19]. According to Seong-Eun et al, age, low body mass index, malnutrition, longer surgery duration and delayed surgery are risk factors for pneumonia [20]. Daniel et al proposed that the risk factors for pneumonia in geriatric patients undergoing surgery for hip fracture are male sex, elderly age, low body mass index and chronic obstructive pulmonary disease [21].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatments are commonly conducted to treat hip fractures, thus about 17,900 female older patients would possibly develop dysphagia after surgery, assuming the prevalence of developing dysphagia was 13%. In particular, dysphagia is a risk factor for aspiration pneumonia, whose reported prevalence after hip fracture surgery was 4.1~11.1% [30][31][32][33]. Aspiration pneumonia was associated with an increase in mortality [31], readmission rates, and sepsis [32].…”
Section: Discussionmentioning
confidence: 99%